Comparison of Tissue Repair with Different Types of Microdissection Tips: A Randomized Histomorphometric Evaluation in Rats - Ana Luiza Vila Verde Brunelli; Luíz Henrique Soares Torres; Arthur Henrique Alécio Viotto; Izabela Fornazari Delamura; Ana Paula Farnezi Bassi; Marisa Aparecida Cabrini Gabrielli; Valfrido Antonio Pereira-Filho (Bioengineering)
The aim of the study was to compare tissue repair of incisions made using different microdissection electrocautery tips in an in vivo animal model. Skin incisions were made, including the subcutaneous tissue, in 30 adult Wistar rats using four types of instruments: a scalpel blade number 15, knife-type electrocautery, microdissection needle, and thin-cut electrode. The animals were divided into five groups based on the euthanasia time—24 h, 48 h, 72 h, 7 days, and 14 days. Each animal received four incisions, one with each type of instrument. Histological and histomorphometric analyses were performed using hematoxylin and eosin (HE) and Picrosirius red stains. Analysis of variance (ANOVA) showed that the type of dissector had no significant effect on type I collagen levels (p = 0.615), whereas the euthanasia time had a significant influence (p < 0.001). Estimated marginal means for type I collagen showed minimal variation among groups, ranging from 35.4% to 36.5%, suggesting limited clinical differences between instruments. These results indicate that while the choice of dissector has a limited impact on type I collagen deposition, time is a determining factor in the wound healing process. The thin-cut electrode enables incisions with tissue repair comparable to that of a number 15 scalpel, as it performs cutting, coagulation, and blending functions at lower temperatures.